Cytoplasmic male sterile gene orf147 of pigeonpea, and uses thereof - International Crops Research Institute for the Semi-Arid Tropics (CGIAR System Organization, 2017)
ICRISAT has adopted the CGIAR IA Principles which require that CGIAR Centers carefully consider whether to register/apply for (or allow third parties to register/apply for) patents and/or PVP over the CGIAR Centers’ respective Intellectual Assets. Under the policy, as a general rule, such applications will not be made unless they are necessary for the further improvement of the Intellectual Assets or to enhance the scale or scope of impact on target beneficiaries, in furtherance of the CGIAR Vision. This disclosure is in fulfilment of the CGIAR IA Principles to provide justifications for the patent applications filed by ICRISAT.